Inhibition of alpha-glucosidases I and II increases the cell surface expression of functional class A macrophage scavenger receptor (SR-A) by extending its half-life. - Tian, G; Wilcockson, D; Perry, V; Rudd, P; Dwek, R; Platt, F; Platt, N (2004)
The class A scavenger receptor (SR-A) is a multifunctional trimeric membrane glycoprotein involved in atherogenesis. The mature receptor can mediate the binding and internalization of a number of specific ligands, including modified low-density lipoprotein. We have investigated the effects of inhibiting N-glycan processing on SR-A expression, distribution, and activity in the murine macrophage cell line RAW264.7. We have found that SR-A normally interacts with calnexin in the endoplasmic reticulum and in its mature form carries complex N-glycans. The imino sugar, N-butyldeoxynojirimycin (NB-DNJ) is an inhibitor of the N-glycan processing enzymes alpha-glucosidases I and II. Following NB-DNJ treatment SR-A became Endo H-sensitive, consistent with inhibition of N-glycan processing. A dose-dependent increase in cell surface expression of SR-A was observed in response to NB-DNJ treatment. The receptor on inhibitor-treated cells was still functional because the increased surface expression resulted in a proportional enhancement in the endocytosis of the ligand, acetylated low-density lipoprotein. The expression of SR-A on NB-DNJ cultured cells was further enhanced by co-treatment with interferon-gamma. Quantitative reverse transcriptase-PCR analysis did not show a significant difference in the amount of SR-A mRNA in NB-DNJ-treated RAW264.7 cells. However, the half-life of SR-A protein was significantly increased. These data indicate the retention of glucosylated N-glycans does not result in gross misfolding and degradation of this receptor or prevent its transport to the cell surface. SR-A interacts with calnexin and when the association is prevented changes in the recycling kinetics and rate of turnover of the receptor result, leading to enhanced cell surface expression.